Aktiviti urusniaga saham menurut perspektif islam - Mohamad Sabri Haron, (Universiti Kebangsaan Malaysia, 2001)
Transaction activities of stocks market are complicated compared with the others. In general, such activities can be divided into two: spot transaction and deferred contracts of exchange. The question arises according to the syariah laws whether the activities of such transactions are permissible or not. This paper embarks to clarify this question under the Islamic perspective of view